Hole‐Transporting Small Molecules Based on Thiophene Cores for High Efficiency Perovskite Solar Cells. Issue 12 (18th September 2014) - Li, Hairong; Fu, Kunwu; Boix, Pablo P.; Wong, Lydia H.; Hagfeldt, Anders; Grätzel, Michael; Mhaisalkar, Subodh G.; Grimsdale, Andrew C.
Abstract Two new electron‐rich molecules, 2, 3, 4, 5‐tetra[4, 4′‐bis(methoxyphenyl)aminophen‐4"‐yl]‐thiophene (H111) and 4, 4′, 5, 5′‐tetra[4, 4′‐bis(methoxyphenyl)aminophen‐4"‐yl]‐2, 2′‐bithiophene (H112), which contain thiophene cores with arylamine side groups, are reported. When used as the hole‐transporting material (HTM) in perovskite‐based solar cell devices, power conversion efficiencies of up to 15.4 % under AM 1.5G solar simulation were obtained. This is the highest efficiency achieved with HTMs not composed of 2, 2′, 7, 7′‐tetrakis(N, N′‐di‐p‐methoxyphenylamine)‐9, 9′‐spirobifluorene (spiro‐OMeTAD) and its isomers. Both HTMs, especially H111, have great potential to replace expensive spiro‐OMeTAD given their much simpler and less expensive syntheses.